Evaluating the Effectiveness of Offsets as a Mechanism for Promoting Malaysian Defence Industrial and Technological Development - Balakrishnan, Kogila (Cranfield University, 2008)
Offsets have taken centre stage in defence trade. To date, more than 78 countries around the world practice offsets and outstanding offsets obligations run into billions of US dollars However, why have offsets gained such a momentum? Increasingly, both sellers and buyers in the arms trade view offsets as an efficient and effective economic compensation tool to justify arms deals. Buyers, consider offsets as a catalyst for industrial and technological development, employment, creation of value-added activities and skills development. Sellers, on the other hand, perceive offsets as providing product differentiation and competitive advantage in an already tough defence market. The question, though is whether, do offsets really work as claimed? The purpose of this dissertation is to empirically verify the above proposition by evaluating the effectiveness of defence offsets in developing a defence industrial and technological base, using Malaysia’s defence industry as a case study. This study employs a Multi-Method or Triangulation Methodological approach (comprising survey, archival sources and participatory observation) to gather data. Fieldwork research employing questionnaires and interviews were undertaken as part of a survey of Malaysian defence companies, international defence contractors and relevant offsets-related government and non-governmental agencies. These data were further substantiated and consolidated via archival sources, such as government and company reports and also participatory observation. Research analysis indicates that offsets have provided mixed results, in the case of Malaysia. The successes have been mainly focused on technology capability-building and human resource development, limited to through-life-support of the defence equipment and the ancillary systems purchased. Morover, offsets have been successfully used to diversify into civil sectors, mainly aerospace and electronics sectors, leading to increased exports, jobs, backward linkages and technology enhancement in these sectors. However, offsets have had minimal effect on creating joint-production, collaborative activities and R&D programmes, requisites for the process of Malaysianisation. Further, offsets have also been less than effective in increasing employment, and dual-use technology programmes that could provide longterm impact on Malaysia’s economic growth. Overall, Malaysia’s offsets policy has been pragmatic and flexible. The government has played a vital role in ensuring that the offsets policy operates in tandem with Malaysia’s national aspirations. Yet, offsets have had a limited impact on developing and sustaining Malaysia’s defence industrial and technology base. The offsets policy aim and objectives have not been clearly reflected in the offsets process and implementation. As defence offsets will continue to be of an essence in Malaysia’s defence procurement activity, initiatives should be taken to review the offsets policy and implementation processes. The review should augment the effectiveness of offsets in developing measurable and value-added programmes that build a sustainable and competitive Malaysian defence industry. To this end, and based on the research findings of this study, a number of important policy recommendations are advanced to raise the effectiveness of Malaysia’s offsets policy.
Cranfield University